Platelets as Scavengers of Neutrophil-Derived Oxidants: A Possible Defence Mechanism at Sites of Vascular Injury - Dallegri, Franco; Ballestrero, Alberto; Ottonello, Luciano; Patrone, Franco (Thrombosis and Haemostasis, 1989)
Platelets (PLTs) were found to inhibit the chemiluminescence (CL) response of neutrophils (neutrophilic polymorphonuclear leukocytes, PMNs) activated with phorbol myristate acetate. The inhibition of the PMN CL response could be efficiently prevented by pulsing PLTs with carmustine (BCNU) to block their glutathione cycle. In ancillary experiments, the CL response of PMNs was inhibited by catalase (H2O2-scavenger), azide (myeloperoxidase-MPO-inhibitor), taurine (hypoclorous acid- HOCL-scavenger) and chloride ion omission. These data suggest that the PMN CL response requires the HOCL production by the following pathway: H2O2 + Cl- HOCL + H2O. Therefore, the BCNU-preventable PLT-induced inhibition of CL may reflect the consumption of PMN-derived H2O2by the PLT glutathione cycle with a consequent impairment of the HOCL production. Consistent with such a possibility, PLTs lowered the H2O2 and HOCL recovery from PMNs via a BCNU-inhibitable process. Based on these results, we suggest that PLTs have the capacity of limiting the oxidant production by PMNs. This PLT capacity may represent a natural device for the protection of vascular structures from PMN-mediated oxidative stresses.
Keywords: Platelets; Neutrophils; Oxidants